Experimental Study of Wear Behavior on Composite Materials under Dry Sliding Conditions - Borneo, Aisyah Noor; Hartono, Daniel Sebastian (RESWARA: Jurnal Riset Ilmu Teknik, 2025)
Dry sliding wear significantly influences the service life of composite materials used in automotive, aerospace, and marine engineering applications. This study presents a comparative experimental investigation of dry sliding wear behavior in various polymer matrix composites and metal matrix composites reported in recent literature. The objective of this study is to synthesize and critically analyze wear trends, dominant mechanisms, and the influence of reinforcement type, load, sliding speed, and filler content on tribological performance. A systematic experimental review methodology was applied by extracting quantitative and qualitative wear data from peer-reviewed journals and classifying them based on material system and test parameters. The analysis shows that hybrid reinforcement systems, such as Si₃N₄–graphite in aluminum matrices and carbon nanotube–alumina in epoxy matrices, consistently exhibit lower wear rates than single-reinforcement systems. Solid lubricants such as graphite and h-BN significantly reduce friction coefficients, while fiber orientation and filler percentage strongly influence wear mechanisms. The findings indicate that optimized hybrid composites can achieve up to 25–40% improvement in wear resistance compared to monolithic materials. This study contributes a structured synthesis of experimental tribological results and provides guidelines for material selection and parameter optimization in dry sliding applications.